(untitled) (Circe de clásicos y modernos, 2018)
This paper analyzes how argentinian nationa-lism designs its own idea of classical tradition in the general context of cultural transfers, with special emphasis on the phenomena of importation and translation. Our hypothesis is that the so-called ‘Western tradition’ –the Greco-Roman heritage and Christianity– is not perceived by the nationalists as an ‘alterity’ but, on the contrary –in essentialist terms– as an origin. Thus we intend to describe the this encounter between classic past and nationalism, and to propose a methodological frame for this nationalist invention of classical tradition.